Inequalities in anemia among Peruvian children aged 6–59 months: A decomposition analysis - Al-kassab-Córdova, Ali; Mendez-Guerra, Carolina; Robles-Valcarcel, Pamela; Iberico-Bellomo, Luis; Alva, Kenedy; Herrera-Añazco, Percy; Benites-Zapata, Vicente A. (Frontiers in Public Health, 2023)
Objective: To quantify the inequalities of anemia in Peruvian children aged 6 to 59 months and uncover its contributing factors. Materials and methods: We conducted a cross-sectional study based on the secondary data analysis of the 2021 Peruvian Demographic and Health Survey (DHS). Our sample included Peruvian children aged 6 to 59 months with complete data for the variables of interest. Anemia was defined as having a hemoglobin level of less than 11 g/dl, adjusted by altitude. Erreygers Concentration Index (ECI) and concentration curves were computed to estimate the socio-economic inequality in anemia among Peruvian children. Moreover, ECI was decomposed to figure out the contributing factors to the inequality of anemia and the residual variation. Results: Nationwide, the prevalence of anemia in Peruvian children was 29.47%. We found a pro-poor inequality regarding anemia at the national level (ECI = -0.1848). The determinants included in the model explained 81.85% of the overall socio-economic inequality in anemia. The largest contribution to inequality was from household- and community-related factors. Having a higher mother´s education level (26.26%) and being from the highlands (24.91%) were the major significant contributors to the overall health inequality. Conclusion: Almost one-third of Peruvian children have anemia. A pro-poor inequality of anemia in Peruvian children was found. Public policies ought to address the major contributing factors of anemia inequality.